Giant prolactinoma with progressive cranial settling and central herniation: a case report - Taha Shahbazi; Soheil Abdollahi Yeganeh; Shiva Borzouei; Mahdi Arjipour (Journal of Medical Case Reports)
Abstract Background Giant prolactinoma (size > 4 cm) is a rare condition and accounts for less than 1% of pituitary adenomas. In even rarer cases, these lesions may involve craniocervical structures requiring surgical intervention. The present case is the largest reported giant prolactinoma (99 × 72 × 57 mm). It led to cranial settling and significant central herniation at the foramen magnum, causing quadriparesis. Case presentation The patient was a 39-year-old Iranian man from a village around Hamadan city who presented with quadriparesis and paresthesia as well as loss of libido and impotence. Magnetic resonance imaging and computed tomography showed a huge diffuse avid enhancing infiltrating osteolytic lesion at the skull base. It had spread predominantly extramurally into the skull base resulting in cranial deposition, significant central herniation, myelopathy, and acute exacerbation of quadriparesis. On the basis of the pathology, immunohistochemistry, and elevated serum prolactin levels, the diagnosis of giant prolactinoma was almost definite. In addition to urgent midline suboccipital craniotomy for the central herniation and quadriparesis, he was treated with cabergoline followed by occiput cervical fixation and fusion to control the progressive subsidence. Conclusion Prolactinoma that is treatable with dopamine agonists should be considered as a differential diagnosis of skull base lesions, even those that are extradural, diffuse, and infiltrative. Giant prolactinoma can lead to craniocervical settling and central herniation that requires surgery and multidisciplinary management.